840kN suspension insulator and preparation method thereof and application to ultra-high voltage power grid
Patent Information
- Application Number
- CN202611184578.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]现有大吨位绝缘子存在诸多技术短板:一是绝缘基体原料配方单一,致密度偏低、抗弯抗拉强度不足,高低温交变环境下热震稳定性差;
1.本发明通过在悬式绝缘子的制备原料中引入纳米氧化铝、纳米二氧化锆及氧化钇稳定助剂对陶瓷基体进行复相改性,配合高压等静压一体成型工艺,提升了绝缘子基体的致密度与微观结构均匀性,结合连接端R12~R16mm圆弧平滑过渡结构设计,消除了传统直角连接处的应力集中现象,经测试,产品额定机械破坏负荷稳定达到840kN以上,抗弯强度超过260MPa,远超传统550kN等级产品,解决了特高压大档距、重覆冰场景下绝缘子机械承载力不足的难题。
Smart Images

Figure CN122991776A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of power transmission and transformation insulation equipment technology, and in particular to an 840kN suspension insulator, its manufacturing method, and its application in ultra-high voltage power grids. Background Technology
[0002] With the large-scale construction of my country's ultra-high voltage backbone power grid, long-distance, large-capacity, multi-split, large-section conductor transmission has become the mainstream. The span of transmission towers is constantly increasing, and the icing load, wind load, and vertical mechanical tension of conductors are also increasing significantly. The mainstream grades of traditional suspension insulators are 300kN, 420kN, and 550kN, which have limited mechanical load-bearing capacity. In areas with large elevation differences, large spans, heavy icing, and strong winds, problems such as head stress cracking, loosening of adhesive, excessive number of strings, and limited tower layout are very likely to occur.
[0003] Existing large-tonnage insulators have many technical shortcomings: First, the raw material formula of the insulation matrix is simple, the density is low, the bending and tensile strength is insufficient, and the thermal shock stability is poor under high and low temperature alternating environment. Secondly, the umbrella skirt structure is fixed, the electric field distribution is uneven, and the failure rate of flashover and ice flashover is high in heavily polluted, coastal salt spray, and industrial dust areas, resulting in a high frequency of operation and maintenance cleaning. Third, large-size insulating blanks are difficult to form, have large sintering deformation, large dispersion of mechanical strength, obvious stress concentration at glued joints, and insufficient reliability for long-term wire mesh operation. Fourth, there is no mature and stable mass production technology for 840kN-class ultra-large tonnage suspension insulators in China. High-end, high-load insulation products rely on external technical support, which restricts the localization and low-cost construction of ultra-high voltage power grid projects.
[0004] Therefore, developing an 840kN extra-large suspension insulator that combines ultra-high mechanical strength, excellent electrical insulation performance, strong weather resistance and pollution resistance, and can be mass-produced industrially is a core technical challenge that urgently needs to be solved in the field of ultra-high voltage power transmission. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the existing technology and to propose an 840kN suspension insulator, its preparation method, and its application in ultra-high voltage power grids.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The 840kN suspension insulator includes a porcelain insulating body, a corrosion-resistant steel foot, a cast steel cap, an inorganic adhesive layer, and a surface functional protective layer. The porcelain insulating body is an integrally formed three-umbrella composite structure, and the connection between the porcelain insulating body and the corrosion-resistant steel foot and cast steel cap adopts a smooth arc transition structure. The inorganic adhesive layer is bonded between the contact surfaces of the ceramic insulating body, the anti-corrosion steel foot, and the cast steel cap. The inorganic adhesive layer is a cement adhesive. The surface functional protective layer consists of a fiber-reinforced transition layer disposed inside the ceramic insulating body and a semiconductor equalizing glaze layer disposed on the surface of the ceramic insulating body.
[0007] Preferred: The raw material formula of the ceramic insulating body is as follows by weight: 42-45 parts of 99.5% pure nano alumina, 5-8 parts of 99% pure zirconium oxide, 6-9 parts of rare earth, 22-25 parts of cordierite, 4-6 parts of barium carbonate, 10-15 parts of feldspar, and electrical ceramic materials with nanocrystals ≤3-5um; The ceramic properties of the ceramic insulation body are as follows: Mohs hardness ≥ 8.5; fracture toughness 8.6 MPa·m1 / 2; water absorption ≤ 0.02% through dense sintering and zero-porosity design; and thermal shock resistance of -40℃ to +70℃ for three cycles without cracking or ceramic chipping.
[0008] Furthermore, the particle size of the raw material powder of the ceramic insulating body is controlled at 3-5 μm.
[0009] Further preferred features include: an overall structural height of 315–330 mm for the ceramic insulating body, a maximum umbrella skirt diameter of 425–440 mm, an umbrella skirt tilt angle of 26°–29°, a center-to-center distance between adjacent umbrella skirts of 85–95 mm, and a connecting end arc transition radius of R12–R16 mm.
[0010] As a preferred embodiment of the present invention: the outermost part of the ceramic insulating body is coated with a nano-hydrophobic and stain-resistant protective coating, and the fiber-reinforced transition layer is composed of epoxy resin, reinforcing fibers and functional fillers.
[0011] The preparation method of an 840kN suspension insulator includes the following steps: S1: Mix the raw materials according to the formula by wet ball milling for 22-26 hours to prepare a uniform ceramic slurry; S2: Ceramic slurry is centrifugally spray-dried and granulated, then dried to produce a special powder for molding; S3: The insulating blank is prepared by isostatic pressing with a high pressure of 145-155MPa. S4: The insulating blank is sintered in a segmented gradient heating manner, with a peak sintering temperature of 1290-1315℃, and then held at a constant temperature for 2-2.8 hours before slow cooling. S5: The sintered insulating blank is polished, glazed, and coated and cured to form a semiconductor equalizing glaze layer on the surface of the ceramic insulating body, thus producing the ceramic insulating body; S6: Subsequently, the surfaces of the anti-corrosion steel foot and the cast steel cap are pretreated by hot-dip galvanizing. Then, high-strength inorganic adhesive is used to automatically glue the porcelain insulation body, anti-corrosion steel foot and cast steel cap, and cure at a constant temperature for 68-76 hours to obtain the finished insulator.
[0012] As a further embodiment of the present invention: in S5, the glaze surface of the insulating blank is first polished, then a uniform glaze is applied to the surface of the insulating blank and cured at low temperature, and then a nano hydrophobic and stain-resistant protective coating is sprayed onto the surface of the insulating blank.
[0013] Based on the aforementioned scheme: In S6, the temperature for constant temperature curing is 10-20℃.
[0014] The 840kN suspension insulator is used in ultra-high voltage power grids. The suspension insulator is applied to 1000kV ultra-high voltage AC transmission lines and ±800kV and above ultra-high voltage DC transmission lines. It is suitable for transmission scenarios with large spans, large elevation differences, heavy icing, coastal salt spray, and heavy industrial pollution.
[0015] The beneficial effects of this invention are as follows: 1. This invention modifies the ceramic matrix by introducing nano-alumina, nano-zirconia, and yttrium oxide stabilizers into the raw materials for suspension insulators. Combined with a high-voltage isostatic pressing integrated molding process, this improves the density and microstructure uniformity of the insulator matrix. Furthermore, the R12-R16mm circular arc smooth transition design at the connection end eliminates stress concentration at traditional right-angle connections. Testing shows that the product's rated mechanical breaking load consistently reaches over 840kN, and its bending strength exceeds 260MPa, far surpassing traditional 550kN grade products. This solves the problem of insufficient mechanical bearing capacity of insulators in ultra-high voltage, long-span, and heavily iced scenarios.
[0016] 2. This invention adopts a three-umbrella gradient arrangement composite umbrella structure, optimizes the umbrella skirt tilt angle and spacing structure, and, together with the semiconductor equalizing glaze layer coated on the surface, can uniformly distribute the electric field on the surface of the insulator, suppress corona discharge and partial discharge phenomena, so that the product has extremely high lightning impulse withstand voltage and power frequency wet flashover voltage in 1000kV UHV AC and ±800kV and above DC transmission lines, ensuring the insulation stability and operational safety of UHV power grids in complex electromagnetic environments.
[0017] 3. This invention applies a nano-hydrophobic and pollution-resistant protective coating to the surface of the suspension insulator. Rainwater alone can wash away surface contaminants, effectively preventing flashover and icing accidents in coastal salt spray, industrial dust, and heavily polluted environments. Simultaneously, the modified ceramic matrix exhibits excellent thermal shock resistance, making it less prone to cracking under severe high and low temperature alternation and icing / melting conditions. This extends the design service life of the suspension insulator to over 50 years, reducing the frequency of high-altitude cleaning and maintenance, and significantly lowering the overall life-cycle maintenance costs.
[0018] 4. This invention integrates advanced processes such as wet ball milling, centrifugal spray granulation, intelligent temperature-controlled segmented sintering, and automated gluing, achieving precise control of the entire process of suspension insulators from raw material processing to finished product assembly. It solves the problems of difficult forming of large-size insulation blanks, large sintering deformation, and large dispersion of mechanical strength, improving the finished product qualification rate while being suitable for large-scale industrial production. It can realize the independent production of ultra-large tonnage insulation equipment, which has important economic significance for reducing the construction cost of my country's ultra-high voltage backbone power grid. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the main structure of the 840kN suspension insulator proposed in this invention; Figure 2 This is a cross-sectional structural schematic diagram of the 840kN suspension insulator proposed in this invention; Figure 3 This is a schematic diagram of the process flow for the preparation method of the 840kN suspension insulator proposed in this invention.
[0020] In the diagram: 1. Porcelain insulating body, 2. Anti-corrosion steel foot, 3. Cement adhesive, 4. Gasket, 5. Cast steel cap, 6. Locking pin, 7. Fiber reinforced transition layer, 8. Nano-hydrophobic and stain-resistant protective coating, 9. Semiconductor equalizing glaze layer. Detailed Implementation
[0021] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0022] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0023] Example 1: 840kN suspension insulator, such as Figure 1-2As shown, it includes a ceramic insulating body 1, a high-strength anti-corrosion steel foot 2, a hot-dip galvanized cast steel cap 5, an inorganic adhesive layer, and a surface functional protective layer; the ceramic insulating body 1 adopts a three-umbrella gradient arrangement composite umbrella structure, which is integrally formed by a large umbrella skirt, a medium umbrella skirt, and a small umbrella skirt. The upper end of the ceramic insulating body 1 is glued to the cast steel cap 5, and the lower end is firmly combined with the anti-corrosion steel foot 2; a fiber-reinforced transition layer is set inside the ceramic insulating body 1, and the adhesive contact surface adopts a smooth arc transition structure.
[0024] The modified raw material formula of the ceramic insulating body 1 is: 42-45 parts of 99.5% pure nano alumina, 5-8 parts of 99% pure zirconium oxide, 6-9 parts of rare earth, 22-25 parts of cordierite, 4-6 parts of barium carbonate, 10-15 parts of feldspar, and electrical ceramic materials with nanocrystals ≤3-5um. The ceramic properties of the ceramic insulating body 1 are as follows: Mohs hardness ≥ 8.5; fracture toughness 8.6 MPa·m1 / 2; water absorption ≤ 0.02 through dense sintering and zero-porosity design; and thermal shock resistance of -40℃ to +70℃ for three cycles without cracking or ceramic chipping. All raw materials are refined through ultrafine ball milling, and the powder particle size is controlled within 3 to 5 μm to ensure uniform powder mixing and sintering activity.
[0025] Structural optimization design parameters for suspension insulators: 1. Overall structural height: 315–330 mm; maximum umbrella skirt diameter: 425–440 mm. 2. The inclination angle of the umbrella skirt is 26°~29°, and the center-to-center distance between adjacent umbrella skirts is 85~95mm; 3. The inner and outer walls of the joint between the porcelain insulating body 1 and the cast steel cap 5 are both made of large arc transition with R12 to R16 mm to eliminate right-angle stress concentration points; 4. The surface of the ceramic insulating body 1 is coated with a composite semiconductor equalizing glaze layer 9, and the outer surface is sprayed with a nano hydrophobic and stain-resistant protective coating 8. The fiber-reinforced transition layer 7 is composed of epoxy resin, reinforcing fibers and functional fillers. Among them, the reinforcing fibers are high-performance ceramic fibers such as glass fiber, carbon fiber, and alumina fiber, and the functional fillers are boron nitride, flame retardants, etc.
[0026] This suspension insulator adopts a three-umbrella composite gradient stress structure, combined with a rounded head transition, nanofiber reinforced core, and multi-layer semiconductor glaze. It simultaneously solves the three major problems of electric field concentration, stress concentration, and pollution deposition. Through nano-multiphase ceramic modification formula, isostatic high-density molding, and rounded stress release structure, the rated mechanical breaking load of the product stably reaches over 840kN, far exceeding the traditional 550kN level products. It can meet the erection requirements of extra-high tension conductors, significantly reduce the number of insulators strung in a single line, and simplify the tower structure design.
[0027] The three-umbrella optimized structure, combined with the surface pressure equalization glaze layer, provides a uniform surface electric field distribution, effectively suppressing corona discharge and partial discharge. The lightning impulse withstand voltage, power frequency wet flashover voltage, and artificial pollution flashover voltage are all significantly improved, resulting in extremely strong insulation stability under ultra-high voltage conditions.
[0028] The outer nano-hydrophobic coating has excellent self-cleaning effect, and rainwater can quickly wash away surface dirt, greatly reducing the frequency of high-altitude cleaning and maintenance; the modified matrix formula significantly improves thermal shock stability, making it less prone to cracking and damage under severe high and low temperature alternation and icing and melting conditions, and its designed service life can reach more than 50 years.
[0029] The top of the anti-corrosion steel foot 2 is firmly fixed to the porcelain insulating body 1 and the cast steel cap 5 by the locking pin 6, thus forming a stable suspension insulator structure. The contact surface between the top of the anti-corrosion steel foot 2 and the inside of the porcelain insulating body 1 is provided with a gasket 4, which can improve the stability of the connection between the anti-corrosion steel foot 2, the porcelain insulating body 1 and the cast steel cap 5.
[0030] Example 2: Method for preparing an 840kN suspension insulator, as follows Figure 3 As shown, it includes the following steps: S1: Batching and grinding: Add the raw material powder into a wet ball mill jar according to the ratio, grind at a uniform speed for 22-26 hours to prepare a uniform ceramic slurry; S2: Spray granulation: The slurry is centrifugally spray-dried to produce solid spherical granulated powder, which is then dried and dehydrated for later use. S3: Isostatic pressing integral molding: Using 145~155MPa high pressure isostatic pressing molding, a complete three-umbrella insulation blank is made in one go, with molding dimensional accuracy ≤±0.5mm; S4: Segmented Precision Sintering: Adopts intelligent temperature-controlled tunnel kiln, segmented gradient heating, maximum sintering temperature 1290~1315℃, constant temperature holding for 2~2.8h, slow cooling to eliminate internal stress; S5: Surface modification treatment: The glaze is polished, a uniform glaze is applied and cured at low temperature to form a semiconductor uniform glaze layer 9 on the surface of the ceramic insulating body 1, and then a hydrophobic and stain-resistant coating is sprayed. S6: Automated gluing assembly: Iron caps and steel feet are pre-treated for corrosion protection, and ultra-high strength and compressive inorganic adhesives are used for automated alignment and gluing. Constant temperature curing is carried out for 68-76 hours to complete the curing. S7: Perform full performance testing on each item and select qualified products for warehousing.
[0031] This method integrates isostatic pressing dry molding, intelligent temperature-controlled sintering, homogenization tempering, and robotic automated assembly into the manufacturing of 840kN-class extra-large tonnage insulators. The molding, sintering, and gluing processes of this preparation method are highly controllable, the mechanical strength of the suspension insulators produced has small dispersion, the finished product qualification rate is high, and it can be upgraded and transformed based on existing electrical ceramic production lines. The industrialization is easy to implement and can quickly replace imported high-end products of the same type.
[0032] The use of the 840kN extra-large insulator of this invention can optimize the overall layout of UHV lines, reduce the number of towers, lower the investment in line foundation construction, and reduce the cost of later operation and maintenance, thereby comprehensively improving the overall safety and economy of the UHV power grid.
[0033] Example 3: The core application scenarios for this suspension insulator are 1000kV UHV AC transmission lines and ±800kV / ±1100kV UHV DC transmission lines. It is particularly suitable for the erection of UHV transmission towers in areas with large spans, large elevation differences, heavy icing, heavy salt spray along the coast, and heavy industrial pollution areas.
[0034] Application Example 1: Using 42 parts of 99.5% pure nano-alumina, 8 parts of 99% pure zirconium oxide, 8 parts of rare earth elements, 24 parts of cordierite, 5 parts of barium carbonate, 13 parts of feldspar, and electrical ceramic materials with nanocrystals ≤3µm, a suspension porcelain insulator was prepared through the following steps: S1: Batching and Grinding: Add the raw material powder into a wet ball mill jar according to the ratio, grind at a uniform speed for 22 hours to prepare a uniform ceramic slurry; S2: Spray granulation: The slurry is centrifugally spray-dried to produce solid spherical granulated powder, which is then dried and dehydrated for later use. S3: Isostatic pressing integral molding: Using 145MPa high-pressure isostatic pressing molding, a complete three-umbrella insulation blank is made in one go, with molding dimensional accuracy ≤ ±0.5mm; S4: Segmented Precision Sintering: Adopts intelligent temperature-controlled tunnel kiln, segmented gradient heating, maximum sintering temperature of 1290℃, constant temperature holding for 2 hours, slow cooling to eliminate internal stress. S5: Surface modification treatment: glaze surface is polished, uniform glaze is applied and cured at low temperature, and then a hydrophobic and stain-resistant coating is sprayed. S6: Automated gluing assembly: Iron caps and steel feet are pre-treated for corrosion protection, and ultra-high strength and pressure-resistant inorganic adhesives are used for automated alignment and gluing. Constant temperature curing is carried out for 68 hours to complete the curing. S7: Each insulator underwent full performance testing, and the electromechanical breaking load of the suspension porcelain insulator was found to be 855kN, and the bending strength was 250MPa.
[0035] The prepared suspension porcelain insulator has a skirt inclination angle of 27°, a skirt spacing of 90mm, and a joint radius of 15mm.
[0036] Application Example 2: Using 43 parts of 99.5% pure nano-alumina, 6 parts of 99% pure zirconium oxide, 7 parts of rare earth elements, 23 parts of cordierite, 3 parts of barium carbonate, 15 parts of feldspar, and electrical ceramic materials with nanocrystals ≤4µm, a suspension porcelain insulator was prepared through the following steps: S1: Batching and Grinding: Add the raw material powder into a wet ball mill jar according to the ratio, grind at a uniform speed for 24 hours to prepare a uniform ceramic slurry; S2: Spray granulation: The slurry is centrifugally spray-dried to produce solid spherical granulated powder, which is then dried and dehydrated for later use. S3: Isostatic pressing integral molding: Using 150MPa high-pressure isostatic pressing molding, a complete three-umbrella insulation blank is made in one go, with molding dimensional accuracy ≤ ±0.5mm; S4: Segmented Precision Sintering: Adopts intelligent temperature-controlled tunnel kiln, segmented gradient heating, maximum sintering temperature of 1300℃, constant temperature holding for 2.5h, slow cooling to eliminate internal stress; S5: Surface modification treatment: glaze surface is polished, uniform glaze is applied and cured at low temperature, and then a hydrophobic and stain-resistant coating is sprayed. S6: Automated gluing assembly: Iron caps and steel feet are pre-treated for corrosion protection, and ultra-high strength and pressure-resistant inorganic adhesives are used for automated alignment and gluing. Constant temperature curing is carried out for 72 hours to complete the curing. S7: Each insulator underwent full performance testing, and the electromechanical breaking load of the suspension porcelain insulator was found to be 860kN, and the bending strength was 255MPa.
[0037] The prepared suspension porcelain insulator has a skirt inclination angle of 27°, a skirt spacing of 90mm, and a joint radius of 15mm.
[0038] Application Example 3: Using 45 parts of 99.5% pure nano-alumina, 8 parts of 99% pure zirconium oxide, 9 parts of rare earth elements, 24 parts of cordierite, 4 parts of barium carbonate, 10 parts of feldspar, and electrical ceramic materials with nanocrystals ≤5µm, a suspension porcelain insulator was prepared through the following steps: S1: Batching and Grinding: Add the raw material powder into a wet ball mill jar according to the ratio, grind at a uniform speed for 26 hours to prepare a uniform ceramic slurry; S2: Spray granulation: The slurry is centrifugally spray-dried to produce solid spherical granulated powder, which is then dried and dehydrated for later use. S3: Isostatic pressing integral molding: Using 155MPa high-pressure isostatic pressing molding, a complete three-umbrella insulation blank is made in one go, with molding dimensional accuracy ≤ ±0.5mm; S4: Segmented Precision Sintering: Adopts intelligent temperature-controlled tunnel kiln, segmented gradient heating, maximum sintering temperature of 1315℃, constant temperature holding for 2.8h, slow cooling to eliminate internal stress; S5: Surface modification treatment: glaze surface is polished, uniform glaze is applied and cured at low temperature, and then a hydrophobic and stain-resistant coating is sprayed. S6: Automated gluing assembly: Iron caps and steel feet are pre-treated for corrosion protection, and ultra-high strength and pressure-resistant inorganic adhesives are used for automated alignment and gluing. Constant temperature curing is carried out for 76 hours to complete the curing. S7: Each insulator underwent full performance testing, and the electromechanical breaking load of the suspension porcelain insulator was found to be 865kN, and the bending strength was 260MPa.
[0039] The prepared suspension porcelain insulator has a skirt inclination angle of 27°, a skirt spacing of 90mm, and a joint radius of 15mm.
[0040] The test data of the suspension porcelain insulators prepared in the above three application examples are summarized in the following table:
[0041] As can be seen from the comparative data of the test structures in the table above, the suspension porcelain insulator prepared by this method overcomes the defects of existing suspension insulators of 550kN and below, such as insufficient mechanical bearing capacity, low electrical withstand performance, weak environmental adaptability, and poor stability of molding and sintering process. It provides an 840kN extra-large suspension insulator with reasonable structure, scientific raw material ratio, and advanced preparation process, which meets the requirements of ultra-high voltage transmission lines for ultra-high tensile bearing, high voltage insulation, and long-term stable operation in complex and harsh environments, and realizes the complete independent production and large-scale engineering application of extra-large tonnage insulation equipment.
[0042] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
A 1.840kN suspension insulator, comprising a porcelain insulating body (1), corrosion-resistant steel feet (2), cast steel caps (5), an inorganic adhesive layer, and a surface functional protective layer, characterized in that... The ceramic insulating body (1) is an integrally formed three-umbrella composite structure. The connection between the ceramic insulating body (1) and the anti-corrosion steel foot (2) and the cast steel cap (5) adopts a smooth arc transition structure. The inorganic adhesive layer is bonded between the contact surfaces of the ceramic insulating body (1), the anti-corrosion steel foot (2) and the cast steel cap (5), and the inorganic adhesive layer is cement adhesive (3). The surface functional protective layer consists of a fiber-reinforced transition layer (7) disposed inside the ceramic insulating body (1) and a semiconductor equalizing glaze layer (9) disposed on the surface of the ceramic insulating body (1).
2. The 840kN suspension insulator according to claim 1, characterized in that, The raw material formula of the ceramic insulating body (1) by mass is as follows: 42-45 parts of 99.5% pure nano alumina, 5-8 parts of 99% pure zirconium oxide, 6-9 parts of rare earth, 22-25 parts of cordierite, 4-6 parts of barium carbonate, 10-15 parts of feldspar and electrical ceramic materials with nanocrystals ≤3-5um. The ceramic properties of the ceramic insulating body (1) are as follows: the ceramic body has a Mohs hardness of ≥8.5; the fracture toughness is 8.6MPa·m1 / 2; the water absorption rate is ≤0.02 through dense sintering and zero-porosity design; the thermal shock resistance is -40℃ to +70℃ for three cycles without cracking or ceramic chipping.
3. The 840kN suspension insulator according to claim 2, characterized in that, The particle size of the raw material powder of the ceramic insulating body (1) is controlled at 3-5 μm.
4. The 840kN suspension insulator according to claim 3, characterized in that, The ceramic insulating body (1) has an overall structural height of 315-330mm, a maximum umbrella skirt disc diameter of 425-440mm, an umbrella skirt tilt angle of 26°-29°, a center-to-center distance between adjacent umbrella skirts of 85-95mm, and a connecting end arc transition radius of R12-R16mm.
5. The 840kN suspension insulator according to claim 4, characterized in that, The outermost layer of the ceramic insulating body (1) is coated with a nano-hydrophobic and stain-resistant protective coating (8), and the fiber-reinforced transition layer (7) is composed of epoxy resin, reinforcing fibers and functional fillers. A method for preparing a 6.840kN suspension insulator, characterized in that, Includes the following steps: S1: Mix the raw materials according to the formula by wet ball milling for 22-26 hours to prepare a uniform ceramic slurry; S2: Ceramic slurry is centrifugally spray-dried and granulated, then dried to produce a special powder for molding; S3: The insulating blank is prepared by isostatic pressing with a high pressure of 145-155MPa. S4: The insulating blank is sintered in a segmented gradient heating manner, with a peak sintering temperature of 1290-1315℃, and then held at a constant temperature for 2-2.8 hours before slow cooling. S5: The sintered insulating blank is polished, glazed, and coated and cured to form a semiconductor equalizing glaze layer (9) on the surface of the ceramic insulating body (1) to make the ceramic insulating body (1). S6: Subsequently, the surfaces of the anti-corrosion steel foot (2) and the cast steel cap (5) are pretreated by hot-dip galvanizing. Then, high-strength inorganic adhesive is used to automatically glue the porcelain insulation body (1), the anti-corrosion steel foot (2) and the cast steel cap (5), and the finished insulator is obtained after constant temperature curing for 68-76 hours.
7. The method for preparing an 840kN suspension insulator according to claim 6, characterized in that, In step S5, the glaze surface of the insulating blank is first polished, then a uniform glaze is applied to the surface of the insulating blank and cured at low temperature, and then a nano hydrophobic and stain-resistant protective coating is sprayed onto the surface of the insulating blank (8).
8. The 840kN suspension insulator and its preparation method according to claim 6, characterized in that, In S6, the temperature for constant temperature curing is 10-20℃. 9.840kN suspension insulators and their application in ultra-high voltage power grids, characterized in that... The suspension insulator is used in 1000kV UHV AC transmission lines and ±800kV and above UHV DC transmission lines. It is suitable for transmission scenarios with large spans, large elevation differences, heavy icing, coastal salt spray, and heavy industrial pollution.